Echiniscus semifoveolatus (Heterotardigrada: Echiniscidae), a newly recorded species from China - Qiao, Penghai; Zhang, Pin; Sun, Xizhai; Li, Xiaochen (Zootaxa, 2013)
Echiniscus semifoveolatus Ito, 1993 (Tardigrada: Echiniscidae) is reported as a new record for China, and was collected from the Mt. Jinggang, Jiangxi, and the Wuyi Mountains, south-eastern China. This is the first report of this species from outside the type locality, Mt. Fuji, central Japan. The number of dorsal spines that arise from the posterior edge of the scapular plate ranges from zero to five while the type specimen has two symmetrically arranged spines at Bd. The distance between the spines varies. These variations in both the number of spines and the distance between the spines could be considered as individual variation. We provide a detailed supplementary description for this species based on the Chinese specimens and supply a key to all known Chinese species of the genus Echiniscus.